2012
DOI: 10.1177/1094670512468294
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Service Quality and Value

Abstract: Electronic service quality (ESQ) is essential for explaining consumer value perceptions in B2C e-commerce contexts. However, we argue that focusing too narrowly on ESQ without considering consumer knowledge-related resources could lead managers to devise myopic strategies. Our research is inspired by, and intends to contribute to, service-dominant logic, service logic, and service science. These perspectives suggest that firms and consumers cocreate value by integrating their resources. However, the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…Consumers' product knowledge influences their evaluation criteria for a given product [60], thus further influencing their purchasing behaviour [28]. In a previous study, Matsumoto et al [28] found that 80% of US consumers have heard about the existence of remanufactured auto parts, whereas only 20% of Japanese consumers have been familiar with the term "remanufactured auto parts".…”
Section: Product Knowledgementioning
confidence: 99%
“…Consumers' product knowledge influences their evaluation criteria for a given product [60], thus further influencing their purchasing behaviour [28]. In a previous study, Matsumoto et al [28] found that 80% of US consumers have heard about the existence of remanufactured auto parts, whereas only 20% of Japanese consumers have been familiar with the term "remanufactured auto parts".…”
Section: Product Knowledgementioning
confidence: 99%
“…The influence of co-creation on trust building and as a signal for assurance and trust, much similar to that of 'brands,' in faceless online transactions is a less understood domain Barrutia, and Gilsanz (2013): Resource integration and the perceived value of websites.…”
Section: Co-creation Examplesmentioning
confidence: 99%
“…We have defined the service innovation as value creation process by players of service structures; value is created for themselves and others, to augments the well-being of all through better processes. (Barrutia & Gilsanz, 2013;Edvardsson & Tronvoll, 2013).…”
Section: Service Innovationmentioning
confidence: 99%